Quality assessment methods to evaluate the performance of edge detection algorithms for digital image: a systematic literature review - Haidi Ibrahim (Tanjung Malim, 2021)
Quality assessment methods to evaluate the performance of edge detection algorithms for digital image: a systematic literature review by Haidi Ibrahim